Fitness to be interviewed: decision-making in the mental health in-patient setting. (March 2021) - Edwards, Allison; Jackson, Simon; Rix, Keith J. B.; Sethi, Faisil
SUMMARY: When a patient in an in-patient psychiatric setting allegedly commits a crime, psychiatrists are sometimes asked to assess their fitness to be interviewed by the police. This article describes how to conduct this assessment, outlines the criminal justice process leading to police interviews (with particular reference to the legal system in England and Wales) and highlights practical issues to consider when assessing fitness to be interviewed in this context.